Estimating the Shelf Life of Instant Tempe in Various Packaging and Storage Temperature using the Arrhenius Model - Thoriq, Ahmad; Khoiris, Daffa; Ciptaningtyas, Drupadi; Pratopo, Lukito Hasta (PERTETA, 2025)
Tempe is a nutritious food that is popular with many people. The problem is that tempe has a short shelf life and must be consumed immediately. Instant tempe is one of the innovative tempe products with a longer shelf life. This research aims to analyze the shelf life of instant tempe in various packages and at different storage temperatures using the Arrhenius model. The method used in this research was laboratory experimental, using 378 samples of instant tempe which were packaged in vacuum packaging, non-vacuum packaging, and cup packaging, and stored at cold temperature (12°C), room temperature (27°C), and hot temperature. (35°C). There are nine treatment combinations regarding the relationship between packaging and temperature, each treatment is carried out 3 times. Measurements for each treatment are carried out until the instant tempe cannot ferment to become tempe ready for consumption. This shows that the fungus Rhizopus oligosporus has died. The research results show that the CIE L* value of instant tempe decreases as the storage period for instant tempe increases. The shelf life of estimation results using the Arrhenius model for vacuum packaging and storage temperatures of 12°C, 27°C, and 35°C respectively is 36.98 days, 6.88 days, and 3.00 days. The use of non-vacuum packaging and storage temperatures of 12°C, 27°C, and 35°C were respectively 15.84 days, 5.63 days, and 2.38 days. In comparison, the use of cup packaging and storage temperatures of 12°C, 27 °C, and 35°C respectively are 17.62 days, 6.31 days, and 2.80 days.